X-ray photoelectron spectroscopy studies of PrAlO3 crystals before and after thermal treatment - Kruczek, Magdalena; Talik, Ewa; Pawlak, Dorota A.; Łukasiewcz, Tadeusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The as-grown PrAlO3 single crystals grown by the Czochralski method are brown colored and after annealing in the reducing atmosphere (20%) H2/N2 they change the color to green. The X-ray photoelectron spectroscopy was used to study the chemical composition and electronic structure of PrAlO3 single crystals before and after the thermal treatment. The core electron lines of praseodymium, aluminum and oxygen were measured and deconvoluted into the synthetic peaks to determine the chemical shifts. The mixed ionic and covalent character of bonds was found. The praseodymium valency may influence the coloration of the PrAlO3 crystal. In the as-grown sample an additional Pr 3d3/2 peak at about 965 eV has higher intensity than that in the annealed one and is attributed to the presence of Pr4+ ions. The measurements showed the reduction of oxygen during thermal treatment and that interstitial oxygen was not removed in this process.
Optica Applicata, Vol. 35, 2005, nr 3, s. 347-354
Keywords: optyka; characterization; praseodymium compounds; perovskites; oxides